Pemanfaatan Visual Literacy melalui Gambar untuk Memotivasi Siswa Belajar Bahasa Inggris - R Agus Budiharto; Laili Amalia; Fujiono Fujiono (Universitas Mathla'ul Anwar Banten, 2019)
USING VISUAL LITERACY THROUGH IMAGES TO MOTIVATE STUDENTS TO LEARN ENGLISH. Existing in an image-rich world, as school students currently experience, does not mean that they naturally possess right visual literacy aptitudes as when they see an object (such as a picture), they just see what they see, they do not possess a considerable capability to understand, interpret, discover a meaning from an object or information they see. For that reason, students are supposed to possess visual literacy to perform that. Given the importance of utilizing visual literacy through a picture to motivate students in learning English, the writer of this article has the initiative to carry out community service to first-grade students of MTS Qurrotul Uyun. This community service discusses the utilization of visual literacy through colored pictures as a pedagogical tool, which can provide a precious and motivating resource for the students to learn English. The result of this community service suggests that English learning through colored pictures is potential to make the MTS Qurrotul Uyun first grade students motivated in learning pronunciation, speaking, and grammar. They feel that English learning through colored pictures in the classroom is more appealing and pleasurable as the pictures can both catch their mind attention and facilitate them to learn. Moreover, the colored pictures can make the MTS Qurrotul Uyun first grade students motivated and more involved actively in English learning.